Neal Whitten's No-Nonsense Advice for Successful Projects - Whitten, Neal (Berrett-Koehler Publishers, 2007)
Learn the Best Practices That Make the Difference Between Troubled Projects and Consistently Successful Projects There's no better way to learn the nuts and bolts of a profession than by having a mentor at your side. But most project managers and leaders don't have that advantage -- and that's why Neal Whitten wrote this book. Having Neal Whitten's No-Nonsense Advice for Successful Projects on hand is like having a mentor to guide you at every turn in the road. Neal shows you how to avoid a painful learning curve with a set of best practices for leading consistently successful projects. In this book, Neal distills his 30 years of experience into tips and strategies that are easy to learn and apply to your projects. These strategies will give you a decisive competitive edge in leading projects and working with stakeholders, clients, and team members. Learn How to: " Run your project like you'd run your own business " Become a "benevolent dictator" for the most effective leadership " Recognize and deal with professional immaturity " Deal with difficult people " Master behaviors that will make your team leaders' jobs easier and benefit your own career " Assess if you're too soft -- and learn to make unpopular decisions if they're necessary to project success " Create a culture that fosters the success of your project " Gain the respect of your team members " Avoid making long-term project commitments " Manage to your top three problems